Association between Parkinson's disease and the risk of adverse cardiovascular events: a systematic review and meta-analysis - Yan Hu; Shanxia Xu (Frontiers in Cardiovascular Medicine, 2023)
BackgroundThis review aims to examine the association of Parkinson's disease (PD) with the increased risk of cardiovascular events.MethodsPubMed, Embase, CENTRAL, and Scopus databases were electronically searched for papers published up to 5 May 2023. Studies reporting the association between PD and the subsequent risks of stroke, myocardial infarction (MI), and cardiovascular mortality were included.ResultsSixteen studies were included in this review. The clinical data of 101,712 PD patients were compared with that of the control group of 204,901 patients without PD in the included studies. Meta-analysis showed that PD patients had an increased risk of stroke compared with patients without PD (odds ratio (OR): 1.49; 95% confidence interval (CI): 1.30, 1.72; I2 = 76%). The pooled analysis demonstrated no significant increase in the risk of MI (OR: 1.16; 95% CI: 0.85, 1.59; I2 = 82%) and cardiovascular mortality (OR: 1.20; 95% CI: 0.93, 1.54; I2 = 65%) in PD patients. However, data from cohort studies indicated a possibility of higher risk of MI (OR: 1.36; 95% CI: 1.01, 1.84; I2 = 80%) and cardiovascular mortality (OR: 1.22; 95% CI: 1.00, 1.60; I2 = 62%) in patients with PD.ConclusionPatients with PD may have an increased risk of stroke as compared with the age- and gender-matched general population. While our results show that PD does not increase the overall risk of MI and cardiovascular mortality, analysis of cohort studies alone demonstrated that these risks may be higher in patients with PD. The current evidence is of very low quality. Further prospective cohort studies from different countries that would account for important cardiovascular risk factors are needed to improve the current evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO (CRD42023421924).